Physical properties (MSCL) of IODP Hole 389-M0099F - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Multi-Sensor Core Logger (MSCL) data (P-wave velocity, magnetic susceptibility, natural gamma radiation (NGR), noncontact resistivity (NCR), gamma ray attenuation (GRA) density) from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). These data were obtained from whole round core sections by means of a Geotek MSCL during the offshore phase of the expedition. The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA. During expedition 389 offshore operations, the recovered cores were transferred from aluminum to plastic liners, thereby draining and to some extent further disturbing the core sections. Thus, partial fluid saturation and drilling-induced core damage on top of natural vugs and fractures common in carbonates and volcanic lava rocks negatively impacted the data quality. GRA density, P-wave velocity, NCR, and magnetic susceptibility were measured every 2 cm, and NGR measurements were obtained every 10 cm. Note, in contrast to standard IODP syntax in this data set the depth value at the end of the sample label identifier, gives the depth in core. For instance, a sample label like 389-M0101B-19-2,126 identifies a measurement from 126 cm depth in core 19 (corresponding to section 2) within hole M0101B of expedition 389. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025